La acción de las ciudades y los gobiernos locales frente a los más graves problemas mundiales de desarrollo - Martín López, Miguel Ángel (Revista Española de Desarrollo y Cooperación, 2023)
Up to now, States and United Nations do not have pay attention to Cities and Local governments for solving the global problems. Nevertheless, they are beginning, in a way descentralized and opens up, to act set against these problems, The purpose of the present work is exactly to show it in the three most important: climate change, hunger and biodiversity.